Project-Based Learning in Environmental Learning: Can It Improve Learners’ Problem- Solving Skills and Mutual Cooperation? - Apriwijayanti, Windasari; Sajidan, Sajidan; Oetomo, Dwi; Widianto Atmojo, Idam Ragil (Pedagogika, 2025)
Problem-solving skills and mutual cooperation of students in class X Senior High School 3 Surakarta, Indonesia are still low categories. This study aims to evaluate the application of the Project Based Learning model on environmental pollution material to improve students’ problem-solving skills and mutual cooperation. This type of research is a class action research conducted at Senior High School 3 Surakarta, Indonesia. The research subjects are X E-2 students. The research procedure includes planning, action, observation, and reflection. Data and sources of research data are questionnaires and tests of problem-solving skills, questionnaires of mutual cooperation, observation sheets of syntax implementation, observation sheets of students’ social interactions, observation sheets of teacher reactions, interview sheets, and documentation. Data collection techniques used questionnaires, tests, observations, interviews, and documentation. Data validation using triangulation techniques. The results showed that the test scores of problem-solving skills increased from 53% in the pre-cycle to 86% in cycle II. All aspects of problem-solving skills and mutual cooperation in cycle II reached the research target. The data shows that applying the Project Based Learning model can improve the problem-solving skills and mutual cooperation of students in class X E-2 Senior High School 3 Surakarta.